Sensitivity and specificity of cerebrospinal fluid flow cytometry for the diagnosis of leukemic meningitis in acute lymphoblastic leukemia/lymphoma. Issue 7 (July 2014) - Mitri, Zahi; Siddiqui, Momin T.; El Rassi, Fuad; Holden, Jeannine T.; Heffner, Leonard T.; Langston, Amelia; Waller, Edmund K.; Winton, Elliott; McLemore, Morgan; Bernal-Mizrachi, Leon; Jaye, David; Arellano, Martha; et al.
Abstract The presence of leukemic blasts detected by light microscopy in cerebrospinal fluid (CSF) establishes the diagnosis of leukemic meningitis in acute lymphoblastic leukemia/lymphoma (ALL). Flow cytometry immunophenotyping (FCI) is a very sensitive method that detects a minute number of aberrant cells, and is increasingly performed on CSF samples. We sought to determine the sensitivity and specificity of CSF FCI for the diagnosis of leukemic meningitis in ALL. Between November 2007 and August 2011, 800 CSF samples from 80 patients with ALL were available from diagnostic lumbar punctures (LPs; n = 80), follow-up LPs (n = 687) and at the time of relapse (n = 33). FCI was performed on 267 samples, and only identified aberrant cells in cytologically confirmed cases of leukemic meningitis. A blinded review of all cases with detectable CSF nucleated cells confirmed these findings. We conclude that CSF FCI has a 100% sensitivity and specificity for the detection of lymphoblasts. However, additional studies are needed to define the role this procedure plays in the diagnosis of leukemic meningitis.